Teaching English to Young Moslem Learners: Lessons Learned from an Expanding Circle Country - Irwansyah, Dedi (JOLLT Journal of Languages and Language Teaching, 2023)
A large number of research projects show an increasing interest in exploring English language teaching for young learners. Until recently, however, there has been little discussion about young Moslem learners who learn English in an expanding circle country. The purpose of this study was to provide a rich description related to the distinctive features of English teaching for young Moslem learners and to describe some plausible English teaching steps for learners. Following a case study design, this article explores informalÂ English teaching involving seventeen young Moslem learners that took place at a mosque located in Lampung province, Indonesia. The researcher played the role of a key instrument who observed and made sense of the teaching process. The findings of the study show that among the noticeable features are dress code and venue, topics, the use of Islamic phrases, and translanguaging. As for the teaching steps, six steps are proposed including opening, performing prayer, storytelling, highlighting high-frequency words, memorizing relevant saying, and closing. This study suggests that the tradition and the linguistic repertoire of the young Moslem learners in the expanding circle country ought to be considered as potential resources to English learning.